Menyelami Kesiapan Guru Kelas Dasar dalam Adopsi Asesmen Diagnostik di Kurikulum Merdeka - Ulfa Laelatul Fitriah; Radeni Sukma Indra Dewi; Ratna Ekawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This research explores the readiness of lower-grade teachers to implement technology-based diagnostic assessments within the Merdeka Curriculum in Indonesia. The curriculum is designed to support flexible and personalized learning; however, its implementation faces various challenges, including a lack of understanding and preparedness among teachers to apply technology-based diagnostic assessments. The methodology employed is a Systematic Literature Review (SLR), which involves five steps: literature search, screening, quality assessment, synthesis of findings, and conclusion. The research process begins with searching for relevant articles through electronic journals, resulting in 358 articles related to teacher readiness. After the screening phase, only 28 articles were selected for further quality assessment. From this number, 5 articles met the relevance and quality criteria for in-depth analysis. The findings indicate that while teachers possess a basic understanding of diagnostic assessments, they still require additional training to enhance their pedagogical competencies and adopt technology in the learning process. This study emphasizes the importance of more intensive training and resource support to facilitate effective implementation of diagnostic assessments. Consequently, it is hoped that educational quality can improve and students can reach their full potential within the framework of the Merdeka Curriculum. These findings provide valuable insights for educational policymakers to design training programs that meet the needs of teachers in the field.